Characterization of the complete chloroplast genome of Poa poophagorum (Gramineae), a native grass from the Qinghai-Tibetan Plateau. Issue 1 (2nd January 2020) - Wei, Linna; Zhang, Chunping; Dong, Quanmin; Yu, Yang; Yang, Xiaoxia
Abstract: This study provides a chloroplast genome of Poa poophagorum . The complete cp genome was135, 664 bp in length with typical quadripartite structure, containing a pair of inverted repeats (IR) of 21, 552 bp each, a large single-copy (LSC) region of 79, 790 bp, and a small single-copy (SSC) region of 12, 770 bp. The overall G + C content of the cp genome was 38.30%, which encompassed 119 genes including 79 protein-coding genes, 8 rRNA genes, and 32 tRNA genes. The phylogenetic analysis indicated that P. poophagorum was closely related to Festuca arundinacea cultivar KY-31in Gramineae. This study would contribute to enrich the Poa L. cp genome resource and promote biological research.